2005
DOI: 10.1097/01.iop.0000155524.04390.7b
|View full text |Cite
|
Sign up to set email alerts
|

Monocanalicular Versus Bicanalicular Silicone Intubation for Nasolacrimal Duct Stenosis in Adults

Abstract: MCI had virtually the same complete success rate as BCI, a higher partial success rate than BCI, and a lower failure rate than BCI in treatment of nasolacrimal duct stenosis in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 18 publications
4
46
0
5
Order By: Relevance
“…We believe its use as the main outcome parameter in this study is justified, because several studies, including ours, have shown a discrepancy between patency and clearance of symptoms of tearing, at least in a subset of patients. 9,15,16 In this study, we found that the lacrimal system was patent in 10 of 16 patients with severe epiphora after treatment. We performed only irrigation tests at three months after surgery and not at long-term follow-up, when data were collected through a telephone survey.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We believe its use as the main outcome parameter in this study is justified, because several studies, including ours, have shown a discrepancy between patency and clearance of symptoms of tearing, at least in a subset of patients. 9,15,16 In this study, we found that the lacrimal system was patent in 10 of 16 patients with severe epiphora after treatment. We performed only irrigation tests at three months after surgery and not at long-term follow-up, when data were collected through a telephone survey.…”
Section: Discussionmentioning
confidence: 78%
“…16 Furthermore, in our hands, the less invasive nature of dacryocystoplasty allows for continuation of anticoagulation and antiplatelet therapy without a significant risk of bleeding. Although silicone tubing may cause complications in itself, 16 these proved relatively minor in our series. Dacryocystoplasty occasionally may prove impossible because of the difficulty in introducing the catheter in the narrowed NLD.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] While bicanalicular intubation has been practiced since the 1970s, monocanalicular intubation did not start to become popular until the 1990s. [11] Both methods have their advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] While bicanalicular intubation has been practiced since the 1970s, monocanalicular intubation did not start to become popular until the 1990s. [11] Both methods have their advantages and disadvantages. [6,8,[10][11][12] In monocanalicular intubations, placement of the tube in the system can be sufficiently performed by entering only one punctum, where the tube is inserted from the upper and lower punctum in the ventricular intubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation